Application of an integrated framework to examine Chinese consumers' purchase intention toward genetically modified food. (April 2018) - Zhang, Yingyu; Jing, Linlin; Bai, Qingguo; Shao, Wei; Feng, Yan; Yin, Shijiu; Zhang, Mengjia
Abstract: The commercial application of transgenic technology in the food industry has become a crucial topic worldwide. This study aims to achieve the following objectives: (i) to examine consumers' purchase intention toward genetically modified (GM) food by using benefit-risk analysis (BRA); (ii) to examine consumers' purchase intention toward GM food based on the theory of planned behavior (TPB); and (iii) to determine which framework or theory significantly influences the interpretation of purchase intention toward GM food under an integrated framework incorporating the BRA and the TPB. An online survey was conducted among 408 qualified samples who were analysed through structural equation modeling. The result analysis leads to the following conclusions: (i) under the BRA framework, Chinese consumers rely on their positive attitude toward GM food to increase purchase intention and their perceived risks to decrease purchase intention. Moreover, consumers' trust increases their perceived benefits offered by GM food and decrease their perceived risks; (ii) under the TPB framework, attitude toward GM technology is the most significant predictor of purchase intention toward GM food, followed by perceived behavioral control and subjective norms; and (iii) under the integrated framework, although most of the results in the single framework of the BRA or the TPB are supported, the BRA provides better interpretation than the TPB. In addition, several mediating effects are found in the context of purchase intention toward GM food.